Prognostic significance of programmed cell death 1 expression on CD8+T cells in various cancers: a systematic review and meta-analysis - Wan, Zhiyong; Cui, Meng; Yang, Jia; Liao, Dan; Chen, Junliang; Li, Fanmin; Xiang, Yin; Cui, Zhiwei; Yang, Yang (Frontiers in Oncology, 2025)
BackgroundIncreased PD-1 expression on CD8+ T cells is considered as a hallmark for T-cell exhaustion, and is thought to be related to the prognosis of cancer patients. However, discrepant results have made it difficult to apply PD-1+CD8+T cells and tumor prognosis to clinical practice. Therefore, we conducted a meta-analysis to evaluate its prognostic value in human cancers.MethodsPRISMA reporting guidelines were strictly followed for conducting the current meta-analysis. The PubMed, Web of Science, Embase databases were searched from inception to November 2024. The pooled Hazard Ratio (HR) along with 95% confidence intervals (CIs) of each article were combined for the associations of PD-1+CD8+ T cells with overall survival (OS), progression- free survival (PFS) and disease-free survival(DFS). Subgroup analyses were performed for area, specimen type, cancer type, treatment, detected method and cancer stage.ResultsA total of 20 studies (23 cohorts, 3086 cancer patients) were included in our study. The expression PD-1+CD8+ T cells in cancer patients tended to predict poor overall survival (OS) (HR: 1.379, 95%CI: 1.084-1.753, p= 0.009), and unfavorable disease-free survival(DFS) (HR: 1.468, 95%CI: 0.931-2.316, p=0.099), though it did not reach statistical significance. Begg’s and Egger’s test demonstrated that no obvious publication bias was exist.ConclusionsHigh PD-1 expression on CD8+ T cells is associated with worse survival outcomes, which can be potentially used as a prognostic marker of malignant tumor.